Ventricular tachycardia ablation in arrhythmogenic right ventricular cardiomyopathy patients with TMEM43 gene mutations. (26th October 2017) - AbdelWahab, Amir; Gardner, Martin; Parkash, Ratika; Gray, Christopher; Sapp, John
Abstract: Introduction: Catheter ablation of VT in patients with arrhythmogenic right ventricular cardiomyopathy (ARVC) is often challenging, frequently requiring multiple or epicardial ablation procedures; TMEM43 gene mutations typically cause aggressive disease. We sought to compare VT ablation outcomes for ARVC patients with and without TMEM43 mutations. Methods: Patients with prior ablation for ARVC‐related VT were reviewed. Demographic, procedural, and follow‐up data were reviewed retrospectively. Patients with confirmed TMEM43 gene mutations were compared to those with other known mutations or who had no known mutations. Results: Thirteen patients (10 male, mean age 49 ± 14 years) underwent 29 ablation procedures (median 2 procedures/patient, range 1–6) with a median of 4 targeted VTs/patient (range 1–9). They were followed for a mean duration of 7.3 ± 4.2 years. Gene mutations included TMEM43 (n = 5), PKP2 (n = 2), DSG2 (n = 2), unidentifiable (n = 4). TMEM patients showed more biventricular involvement compared to non‐TMEM patients (80% vs. 12.5%, P = 0.032), more inducible VTs during their ablation procedures (mean VTs/patient: 5.8 ± 3 vs. 2.6 ± 1, P = 0.021). Acute and long‐term procedural outcomes did not show a significant difference between the two groups, however TMEM patients had worse composite endpoint of death or transplantation (60% vs. 0, P = 0.035; log‐rank P = 0.013). Conclusions: TMEM43 mutation patients were more likely to have biventricular arrhythmogenic substrate and more inducible VTs at EP study. Despite comparable acute VT ablation outcomes, long‐term prognosis is unfavorable.